Trader participation in the governance of markets in Johannesburg: the case of Bree and Midrand markets - Daniel, Marie (My University, 2017)
Urban governance in many cities of the global South is subject to two dynamics. The first is a process of neoliberalisation, consisting inter alia of an emphasis on business principles to manage public assets; the quest for cost recovery; and forms of privatisation or delegation of management of specific spaces or services. The second is a process of democratisation, where participatory planning and governance, decentralisation and the quest for locally-adapted and responsive solutions to urban issues, are characterising public discourses. The management of markets as profit-making spaces of trade often occupying public spaces and considered a key function of cities is the site of such dynamics. All the stakeholders involved in market governance need to sustain themselves and their institutions through revenues or income. Terms such as participation and empowerment can become a rhetoric used to mask revenue objectives and co-opt traders into meeting them. Through the case studies of Midrand and Bree markets in the City of Johannesburg, the research argues that traders are participating in market governance, through representative collectives, without clarity over what they are participating in. They have been convinced to participate by other stakeholders that have their own potential interests. It is argued that in a sector where traders are struggling to survive an ambitious drive should be welcomed but that the overwhelming focus on economic empowerment is a matter of concern. There is also a need for the development of political capabilities. Within such a context there is potential to see the entanglements between neoliberalisation and participation enhance the democratisation of market governance.
A Research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg. In fulfilment of the requirements for the Master of Urban Studies. Johannesburg, 24 May 2017
Keywords: Management--Employee participation; Communication in industrial relations